PERAN SERTA IBU MENGHINDARKAN KELUARGA DARI RESIKO PENYAKIT BAWAAN MAKANAN (FOODBORNE DISEASE) - Fauziyah, Begum (EGALITA, 2010)
Recently, we often hear that government have announced about 2010 health indonesian programme. The aim of this programme is to create health indonesian people and good in quality human. One of the key to success this programme is fullfill food which save, health and permitted for indonesian people. Food is important needed for people to life. So, people must consume good and health food to make good quality human. Save, health and permitted food is food that did’nt contain or free from biological contaminant, chemical contaminant or materials that can loss and damage human health. The health interference that is caused by contaminant in food is called by foodborne disease. The indications of this disease are queasy, throw up, diarrhea, cramps in stomach and fever. Because of that, it needs control and analysis in each step of food chain. As we know, food chain contain of quality repairing step of food raw materials, control contaminant step in food technology and food preparation step to be consumed. All of those steps need to control and analysis of contaminant to make sure that food in good and health condition to be consumed. According to Nature theory, Functional theory and Islamic perspective, a housewife has duty to manage family needed especially cooking. Back to the food chain, a housewife has urgent role in the third step of food chain. It means, a housewife has urgent role to create health and good quality of family and save family from foodborne disease. Because of that, a housewife has to know about foodborne disease, hygiene procedure in food preparation process and saving food procedure.Keywords : foodborne disease, contaminant, food chain, hygiene procedure.